Cuentos regionales y lectura oral en niños de cinco años de la Institución Educativa Inicial N° 728 Ramón Castilla 2021 - Meregildo Chichipe, Maria Isabel (2024)
The objective of the research was to relate regional stories and oral reading in fiveyear-old children of the Initial Educational Institution No. 728 of Ramón Castilla in 2021. The non-experimental, bivariate, cross-sectional, and field study design was used, applying the type of relational research. The children belonging to the educational institution were the sample and population, being 78. Observation guides were prepared that served as instruments for data collection, subjected to expert judgment before applying them, which was done through the technique of observation. The results show a relationship between the application of regional stories and oral reading in the 78 (100.0%) children of the Initial Educational Institution No. 728 "Ramón Castilla", where it is observed that 2 (2.6%) with level beginning of oral reading present a deficient level of application of regional stories. Of the 34 (43.6%) children with a level in progress in oral reading, 20.5% (n=16) have deficient application, 11.5% (n=9) have a regular level and 11.5% (n=9) good level of application of regional tales. Of the 42 (53.8%) with an expected level of achievement in oral reading, 12.8% (n=10) show a regular level and 41.0% (n=32) a good level of application of regional tales. In other words, with a good application of the regional stories, the best level of oral reading in children.